2016
DOI: 10.3389/fpls.2016.00327
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Sensors as Key Hubs in Plant Responses to Biotic and Abiotic Stresses

Abstract: The Ca2+ ion is recognized as a crucial second messenger in signaling pathways coupling the perception of environmental stimuli to plant adaptive responses. Indeed, one of the earliest events following the perception of environmental changes (temperature, salt stress, drought, pathogen, or herbivore attack) is intracellular variation of free calcium concentrations. These calcium variations differ in their spatio-temporal characteristics (subcellular location, amplitude, kinetics) with the nature and strength o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
206
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(212 citation statements)
references
References 74 publications
1
206
0
5
Order By: Relevance
“…Increasing evidence indicates that calcium plays an import role in flavonoid biosynthesis. It has been reported that the calcium can regulate anthocyanin accumulation, possibly by activating flavonoid pathway genes495051. Several components of calcium signaling pathway such as Ca 2+ , calmodulin, and protein kinases have been shown to be involved in regulating the anthocyanin level515253.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence indicates that calcium plays an import role in flavonoid biosynthesis. It has been reported that the calcium can regulate anthocyanin accumulation, possibly by activating flavonoid pathway genes495051. Several components of calcium signaling pathway such as Ca 2+ , calmodulin, and protein kinases have been shown to be involved in regulating the anthocyanin level515253.…”
Section: Discussionmentioning
confidence: 99%
“…As sessile organisms, plants have evolved various strategies to withstand these adverse environmental conditions (Komatsu and Hossain, 2013; Ranty et al, 2016). The survival of plants against these environmental stresses depends on their ability to recognize stress stimuli and adapt to such stresses by regulating the expression of stress-responsive genes in cellular organelles, nucleus, and cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…The Ca 2+  is a second messenger in signalling network coupling the perception of a stressful environment to a significant plant adaptability (Tuteja and Mahajan 2007; Marco et al 2015). Ca 2+  acts at the crossroads of various signalling pathways (Gill and Tuteja 2010; Rany et al 2016). High-salinity stress initiates the calcium signalling network (Tuteja 2009), inducing membrane depolarization, and may activate sensitive Ca 2+  channels to generate a Ca 2+  signature (Tester and Davenport 2003; Zhu 2003).…”
Section: Introductionmentioning
confidence: 99%